2 answers:
Answer: 2
Explanation:
The average rate of change is the net change of the function, i.e. final value less initial value, divided by the interval:
f(b) - f(a) f(1) - (f(-3)
average change rate from a to b = ---------------- = ---------------
b - a 1 - (-3)
f(1) = -(1/2) (1 + 2)² + 5 = -(1/2) (3)² + 5 = 5 - 9/2 = 1/2
f(-3) = -(1/2) ( -3 + 2)² + 5 = -(1/2) (-1)² + 5 = 5 - 1/2 = 9/2
(1/2) - (9/2)
average change rate = -------------------- = 2
1 - 3
That is the answer.
Here are a ton of correct answers. I got a few questions wrong but they still show the correct answer.
You might be interested in
Answer:
Step-by-step explanation:
Answer:
hi
Step-by-step explanation:
13×4=52
area is 52
have a nice day
8. 6m + 3n
11. 8r^3 - r^2
12. 3h^2 + 8
hope this helps !
Answer:
2/3
Step-by-step explanation:
Less than 5 is 1,2,3,4 and 4 out of 6 is also equal to 2/3
6x-9x-4=-2x-2
3x-4=-2x-2
3x+2x=-2+4
5x= 2
x=2/5